Islam, Peace and Social Justice: A Christian Perspective (N/a, 2014)
Front cover -- Title page -- Copyright -- Contents -- Acknowledgments and Dedication -- Foreword by David W. Shenk -- Introduction -- 1. Islam's Divine Mandate for Ethical Action against Social Injustice -- 2. Islamic Jihad and the Path of Peace -- 3. Islamic Responses to Poverty and Economic Oppression -- 4. Islamic Responses to Political Oppression -- 5. Islamic Civil Rights and Individual Human Rights -- 6. Genocide and Atrocity among Muslims -- 7. Islamic Social Equality in Response to Racism and Slavery -- 8. Sexual Injustice, Sexism and Homophobia among Muslims -- 9. Islamic Stewardship and Responses to Environmental Degradation -- 10. Creating Multifaith Social Justice Partnerships -- Conclusion -- Notes -- Introduction -- 1. Islam's Divine Mandate for Ethical Actionag ainst Social Injustice -- 2. Islamic Jihad and the Path of Peace -- 3. Islamic Responses to Poverty and Economic Oppression -- 4. Islamic Responses to Political Oppression -- 5. Islamic Civil Rights and Individual Human Rights -- 6. Genocide and Atrocity among Muslims -- 8. Sexual Injustice, Sexism, and Homophobia among Muslims -- 9. Islamic Stewardship and Responses to Environmental Degradation -- 10. Creating Multifaith Social Justice Partnerships -- Conclusion -- Glossaries -- Glossary of Terminology -- Glossary of Arabic and Persian Terms -- Glossary of Names and Events -- Selected Bibliography -- Back cover.